2019
DOI: 10.12955/cbup.v7.1382
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Brand in Consumer Buying Behavior and Product Quality Assesment

Abstract: In order to maintain or increase market share, every company tries to use the most optimal combination of marketing communication tools or marketing mix tools. There are a large number of products placed on the market from a large number of companies that need to distinguish one another from competing companies. The most important tool to differentiate from competitors is the brand of products. The aim of each company is to ensure that their product brand is brought to the attention of customers and that custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Unsurprisingly, brand was the most considered product factor, which agrees with previous studies [69][70][71]. Brand serves as a sign of quality and helps effectively differentiate products with similar physical characteristics [72,73]. In this study, the variation in milk choices, including between genders and ages and across cities, could all be associated with brand familiarity to some extent.…”
Section: Product Factors Considered For Self-consumptionsupporting
confidence: 88%
“…Unsurprisingly, brand was the most considered product factor, which agrees with previous studies [69][70][71]. Brand serves as a sign of quality and helps effectively differentiate products with similar physical characteristics [72,73]. In this study, the variation in milk choices, including between genders and ages and across cities, could all be associated with brand familiarity to some extent.…”
Section: Product Factors Considered For Self-consumptionsupporting
confidence: 88%
“…Research has confirmed the positive relationship of image on customer satisfaction (Chusnaini and Rasyid and Candraningrat, 2022;Kim et al, 2016). This relationship is quite strong, both in the industry model and in Apple and Samsung smartphone models, which corresponds to the strength of the image itself (especially brand image) of the three strongest manufacturers: Apple, Samsung and Huawei, and explains the weak impact of Xiaomi a customer satisfaction due to weak brand image (Valjaskova and Kral, 2019).…”
Section: The Smartphone Industrymentioning
confidence: 78%
“…A brand helps with product differentiation by distinguishing one product from another and creating a competitive advantage (Valjaskova and Kral, 2019) [52] . This allows companies to stand out in a crowded market and ensure that their products are perceived as unique and high quality (Dirisu et al, 2013) [12] .…”
Section: Role Of Geographical Indications As a Branding Strategy For ...mentioning
confidence: 99%